How Can We Define “Optimal Microbiota?”: A Comparative Review of Structure and Functions of Microbiota of Animals, Fish, and Plants in Agriculture - Ikeda-Ohtsubo, Wakako; Brugman, Sylvia; Warden, Craig H.; Rebel, Johanna M. J.; Folkerts, Gert; Pieterse, Corné M. J. (Frontiers in Nutrition, 2018)
All multicellular organisms benefit from their own microbiota, which play important roles in maintaining the host nutritional health and immunity. Recently, the number of studies on the microbiota of animals, fish, and plants of economic importance is rapidly expanding and there are increasing expectations that productivity and sustainability in agricultural management can be improved by microbiota manipulation. However, optimizing microbiota is still a challenging task because of the lack of knowledge on the dominant microorganisms or significant variations between microbiota, reflecting sampling biases, different agricultural management as well as breeding backgrounds. To offer a more generalized view on microbiota in agriculture, which can be used for defining criteria of “optimal microbiota”and can be set as the goal of manipulation, we summarize here current knowledge on microbiota on animals, fish and plants with emphasis on bacterial community structure and metabolic functions, and how microbiota can be affected by domestication, conventional agricultural practices and use of antimicrobial agents. Finally, we discuss future tasks for defining “optimal microbiota”, which can improve host growth, nutrition and immunity and reduce the use of antimicrobial agents in agriculture.